2015
DOI: 10.4238/2015.december.9.6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA-106b and its clinical significance in cutaneous melanoma

Abstract: ABSTRACT. is overexpressed in various types of cancers and is associated with the regulation of carcinogenic processes. However, its clinical significance in cutaneous melanoma has not been reported. qRT-PCR was performed to examine the expression of miR-106b in 15 cases of dysplastic nevi, 17 cases of melanoma metastases, and 97 cases of primary cutaneous melanoma tissue samples. Survival rate was determined with Kaplan-Meier and statistically analyzed with the log-rank method between groups. Survival data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…A large number of experimental studies have demonstrated that miR-126-3p, beside regulating angiogenesis and vessel integrity, acts as a tumor suppressor in a variety of tumors, including melanoma, through negative modulation of proliferation, migration and invasion [26, 42, 56]. Moreover, Lin et al [57] demonstrated a progressive decrease of miR-126-3p levels in dysplastic nevi, primary melanomas and melanoma metastases and a shorter 5-years overall survival in patients with primary tumor expressing low miR-126-3p levels. Down-regulation of miR-126-3p has also been implicated in acquired resistance of cervical cancer cells to TRAIL [58], and of gastric cancer cells to vincristine and adriamycin [59].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of experimental studies have demonstrated that miR-126-3p, beside regulating angiogenesis and vessel integrity, acts as a tumor suppressor in a variety of tumors, including melanoma, through negative modulation of proliferation, migration and invasion [26, 42, 56]. Moreover, Lin et al [57] demonstrated a progressive decrease of miR-126-3p levels in dysplastic nevi, primary melanomas and melanoma metastases and a shorter 5-years overall survival in patients with primary tumor expressing low miR-126-3p levels. Down-regulation of miR-126-3p has also been implicated in acquired resistance of cervical cancer cells to TRAIL [58], and of gastric cancer cells to vincristine and adriamycin [59].…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of included studies included in the present analysis was summarized in Table 1 and Table 2 . Of these 26 studies, 20 [ 15 , 17 , 21 30 , 32 37 , 39 , 41 ] studies were conducted among the Asian, and the rest [ 16 , 20 , 31 , 38 , 40 , 42 ] were among the Caucasian. Besides this, 21 [ 16 , 17 , 20 23 , 27 29 , 31 42 ] studies used tumor tissues to detect miRNAs concentrations, 4 [ 15 , 24 26 ] studies used blood samples, and 1 [ 30 ] study tested in both tissue and serum samples.…”
Section: Resultsmentioning
confidence: 99%
“…We extract data from these 26 studies, which included 3189 participants in total. The type of cancers assessed in these studies included colorectal cancer (CRC) [ 20 25 ], lung cancer [ 15 , 26 , 27 ], hepatocellular carcinoma (HCC) [ 17 , 28 , 29 ], breast cancer (BC) [ 16 , 30 ], esophageal squamous cell carcinoma (ESCC) [ 31 , 32 ], glioma [ 33 , 34 ], pancreatic cancer (PC) [ 35 , 36 ], BL (including T-cell lymphoblastic lymphoma [ 37 ], Burkitt lymphoma [ 38 ]) and others (astrocytoma [ 39 ], gastrointestinal cancer [ 40 ], melanoma [ 41 ], and ependymomas [ 42 ]). Quantitative real-time PCR (qRT-PCR) was used in 25 studies to assess miRNA expression, and only 1 study exploited microarray analysis.…”
Section: Resultsmentioning
confidence: 99%
“…87 Expression of various miRNAs at abnormal levels has been shown to correlate with disease stage and recurrence. 88,89 Finally, circulating tumor DNA (ctDNA) found in the plasma has been investigated as a means to determine disease status in patients with advanced melanoma. 90 This ctDNA can both provide insights into total tumor load and into tumor-associated mutations.…”
Section: 77mentioning
confidence: 99%